2021
DOI: 10.1515/gps-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

Foliar applications of plant-based titanium dioxide nanoparticles to improve agronomic and physiological attributes of wheat (Triticum aestivum L.) plants under salinity stress

Abstract: The present study was carried out to investigate the beneficial and toxicological effect of plant-based titanium dioxide nanoparticles (TiO2 NPs) on the morphophysiological attributes of wheat plants under salinity stress. The biogenesis of titanium dioxide nanoparticles was accomplished by using the extract of Buddleja asiatica L. leaves followed by characterization through UV visible spectroscopy, SEM, FTIR, and EDX. NaCl salt was applied in two different concentrations after 21 days of germination followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Moreover, some of the TiO 2 NPs are fused and form tiny aggregations. Our findings are in accordance with those of Mustafa et al [42] and Rajakumar et al [43].…”
Section: Sem and Tem Analysis Of Green Synthesized Tio2 Npssupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, some of the TiO 2 NPs are fused and form tiny aggregations. Our findings are in accordance with those of Mustafa et al [42] and Rajakumar et al [43].…”
Section: Sem and Tem Analysis Of Green Synthesized Tio2 Npssupporting
confidence: 94%
“…Our results are inlined with results of Dobrucka [39] and Satti et al [40] who showed maximum absorption of TiO 2 NPs at this range using Echinacea purpurea and Moringa oleifera leaf extract respectively. While those synthesized by Vijayalakshmi and Rajendran [41] and Mustafa et al Chrysin ND [42] revealed maximum absorption peak between 300 and 400 nm. These differences may be attributed to the sensitivity of the UV spectrum to many factors such as shape, size, and agglomeration of the particles as recently confirmed [29].…”
Section: Spectrophotometric Analysis Of Green Synthesized Tio2 Npsmentioning
confidence: 97%
“…The yield and biomass of plants are directly related to the uptake of vital nutrients that play numerous important roles in plant metabolism, and their absence or deficiency also results in deterioration effects on plant growth and development according to ref. [ 6 ]. In the present study, salinity stress reduced the yield attributes of wheat varieties, as this stress causes a deficiency of nutrients, such as potassium, phosphorus and nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous abiotic stresses are threatening wheat productivity in major wheat-growing countries, which include the USA, Russia, Pakistan, China, India and Australia [ 5 ]. Among the different abiotic stresses, soil salinity is among the most severe agricultural constraints throughout the world [ 6 ]. Salinity is amongst the most crucial elements in climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, Gohari et al (2020) noticed that the greatest agronomics character (leaf weight, leaf number and plant height) was noticed in 100 mg/l TiO2-treated under control conditions. Likewise, Mustafa et al (2021) who observed 40 mg/l of TiO2NPs is effective to enhance the morphophysiological attributes, that is; fresh and dehydrated weight, chlorophyll contents, leaves No./plant, length of root, shoot beside whole plant. Nonetheless, higher concentration which is 60 as well as 80 mg/l, wheat cultivars suffered a detrimental impact.…”
mentioning
confidence: 95%